1997
DOI: 10.1021/jp962408h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assembly Structure of CCl4 in Graphitic Nanospaces

Abstract: The X-ray diffraction of CCl4 molecules adsorbed in slit-shaped graphitic micropores was measured at 303 K. The effect of the pore width in the range of 0.75−1.13 nm on the structure of CCl4 molecular assembly in the micropores was examined. The electron radial distribution function (ERDF) analysis was applied to the diffraction data, and the ERDFs from only adsorbed molecular assembly were determined. The peak position of ERDF due to the first-nearest-neighbor coordination agreed with that of the bulk liquid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 33 publications
1
68
1
Order By: Relevance
“…The temperature dependence of the ERDFs of water molecules in A25 micropores at φ = 0.85 are shown in Figure 7, which also shows the ERDFs of bulk water at 298 K. Details of the ERDF derivation were provided in our previous work. 16 The ERDF of bulk water shows three peaks at 0.30, 0.42, and 0.70 nm, corresponding to the first, second, and third nearest neighbours of water molecules, respectively. This indicates that water does not possess long-range order longer than 0.8 nm.…”
Section: Radial Distribution Function Of Confined Watermentioning
confidence: 99%
“…The temperature dependence of the ERDFs of water molecules in A25 micropores at φ = 0.85 are shown in Figure 7, which also shows the ERDFs of bulk water at 298 K. Details of the ERDF derivation were provided in our previous work. 16 The ERDF of bulk water shows three peaks at 0.30, 0.42, and 0.70 nm, corresponding to the first, second, and third nearest neighbours of water molecules, respectively. This indicates that water does not possess long-range order longer than 0.8 nm.…”
Section: Radial Distribution Function Of Confined Watermentioning
confidence: 99%
“…The XRD profiles were corrected by an appropriate method, and the scattering intensity from adsorbed CHCl 3 assembly was extracted from the XRD profiles corrected by subtraction the diffraction data of carbon itself. The experimental setup and extracting methods were already published in the previous article (Iiyama et al, 1997b).…”
Section: Methodsmentioning
confidence: 99%
“…micropore width in the range of 1 to 2 molecular diameters (Iiyama et al, 1997b;Suzuki et al, 1999). In the CHCl 3 -W10 system, the adsorbed molecules form ordered structure in which the dipole stands in vertical to the carbon surface and an anti-parallel side-by-side order.…”
mentioning
confidence: 99%
“…20 Here a plastic crystal is defined as a special solid phase having long-range positional order for the center of the molecules, but only shortrange orientational order. GCMC simulation and in situ X-ray diffraction studies have shown that the plastic crystal phase is stable in slit-shaped pores of ACF whose width is smaller than 1 nm at 303 K. 21 This indicates the transition temperature of the plastic crystal in the micropores is shifted by 53 K at least. Thus, nanoconfinement induces a marked enhancement of the collective interaction between molecules, stabilizing the low-temperature phase.…”
Section: In-pore Phase Anomalymentioning
confidence: 99%